DEVELOPMENT OF INDUCTION TECHNOLOGY ON AGARWOOD CULTIVATION - A REVIEW - I Gde Adi Suryawan Wangiyana (JURNAL SANGKAREANG MATARAM, 2020)
Agarwood is one of high valuable non-timber forest commodity produce by family thymeleaceae, especially genus Aquilaria and Gyrinops. Agarwood commodity on the market only could be sold from cultivated species. Thus, agarwood cultivation method should be fully understood by agarwood farmers and agarwood researchers. Induction technology is one of the most important things on agarwood cultivation method. Induction procedure could induce resin production on agarwood cultivated species. This resin has an aromatic fragrance which well known as “gubal” on the market. It is imposible for cultivated agarwood species to produce gubal without induction process. Induction tehnology has been developed form old traditional method into new modern method. Each method has seraval advantages and disadvantages. Old traditional method induced agarwood physically using traditional equipment such as: machete, chopper and nail. It is simple method but only produce resin in very small area. Modern method induces agarwood using chemical liquid or microorganism culture that could spread all over agarwood stem. This method could induce resin in a very wide area compare to traditional method. Resin productivity using modern method is higher than those traditional methods. Thus this modern method induction technology could be best solution for agarwood farmers to increase their agarwood resin.